UTHM Student Driver Hub Booking System - Halim, Sofia Adlina; Mohd Salikon, Mohd Zaki (Applied Information Technology And Computer Science, 2025)
It is critical to find creative solutions in the ever-changing field of higher education that meet the varied and changing demands of students. In order to improve the mobility, safety and trust of Universiti Tun Hussein Onn Malaysia (UTHM) students, this project introduces the "UTHM Student Driver Hub Booking System," a transportation management system. Designed with user authentication, safety and inclusion, this system provides an easy-to-use platform that manages the booking of trips within and around the UTHM campus. The system, which is run by committed administrators, provides UTHM students with the ability to operate as drivers and provides safe, practical, and uniform transportation services. UTHM students’ unique needs are handled by the system using the Prototyping Model, an iterative system development process that actively incorporates users. To make the user interface looks slick and up to date, Flutter framework is used. Furthermore, this project was developed using Android Studio along with Firebase as its Cloud Firestore. This project demonstrates the potential of innovation to improve the student experience while also marking a step forward in the redefining of campus mobility services.